A Novel Signal Processing Technique for Separating Tonal and Broadband Noise Components from Counter-Rotating Open-Rotor Acoustic Data. Issue 1 (January 2013) - Sree, Dave
Renewed interest in counter-rotating open-rotor technology for aircraft propulsion application has prompted the development of advanced diagnostic tools to enable improved design and improved acoustical performance of open rotors. In particular, the determination of tonal and broadband components of open-rotor noise spectra is essential for properly assessing the noise control parameters and for validating noise prediction codes. Techniques that have been successfully used for processing acoustic data from single rotors (fans, propellers, etc.) do not work well for counter-rotating open-rotor systems in that the tonal and broadband noise components cannot be separated from raw acoustic data properly, particularly when the two rotors are driven independently without synchronization. The need for a new signal processing tool for counter-rotating open rotors was thus envisioned and is presented in this work. The new technique has been verified to perform well against simulated data as well as real acoustic data available from scale-model open-rotor tests at NASA-Glenn Research Center. Based on the results, the applicability and limitations of the technique are discussed in the paper.